Public art and museums in cultural districts - Lorente, Jesús Pedro, 1963- (Routledge, Taylor & Francis Group, 2019)
"This book reviews their changing interactions in many different types of cities since the Enlightenment, or even before, going back to the etymological origins of museums and monuments in classical antiquity"-- Resumé vydavatele
Keywords: public art; muzea; umění a společnost; museums; art and society; monografie; monographs